Tracking and explaining credit-hour completion - Maxwell Ndigume Kwenda (Laureate Education Inc, 2014)
This study highlights factors associated with changes in earned hours for two cohorts of incoming freshmen during their first year. The objectives of this study are twofold: (a) to derive model(s) regressing the cumulative hours earned and differential hours earned on student demographic, socioeconomic, and academic characteristics; and (b) to provide succinct conclusions that will increase students' satisfactory academic progress (SAP) based on the results. The study sample of 1,598 cases is made up of students from two cohorts of first-time, four-year degree-seeking students who started in the Fall semesters of 2010 and 2011, respectively. There were two measures of the dependent variable: Cumulative hours earned and the difference in earned hours between the Fall and Spring semesters. Multiple linear regression was used to explain the outcome variables using a student's demographic, socioeconomic, and academic characteristics. The study found that there have been changes at Cameron University related to the freshman first year experience, while there were no significant differences detected between the 2010 and 2011 cohorts. In addition, demographic variables generally did not significantly explain earned hours or changes in earned hours. The significant predictors were generally tied to a student academic standing or factors for which the institution can exercise some control. DOI: 10.18870/hlrc.v4i1.132